OPTIMALISASI MEDIA DIGITAL QUIZLET SEBAGAI MEDIA PEMBELAJARAN BIPA UNTUK KETERAMPILAN BERBAHASA - Pradiani, Yulia Ika Putri; Amalia , Zarya; Mirnawati, Mirnawati; Muzaki, Helmi (Hasta Wiyata, 2024)
BIPA learning is growing rapidly, with many foreign speakers who have an interest in learning Indonesian. Innovation in BIPA learning is needed, and one of the innovations is utilising digital media in the form of applications and web that provide interesting features and can be utilised in learning. The Quizlet application is one of the digital media that can be used for learning because it has various features. This research aims to describe the use of Quizlet in BIPA learning. This research uses a qualitative approach with a literature study method. In this study, researchers used similar studies or studies that have a relationship with the use of Quizlet applications as BIPA learning media. The results of this study indicate that Quizlet has features that can be used as a BIPA learning medium for language skills. The features that can be used as a medium of learning include flashcards, learn, spell, write, test, and match. This study also shows that the Quizlet application can be used to support learners’ mastery of new vocabulary and terms.